2016
DOI: 10.1111/ivb.12129
|View full text |Cite
|
Sign up to set email alerts
|

Spawning of coral reef invertebrates and a second spawning season for scleractinian corals in the central Red Sea

Abstract: Recent coral spawning observations in the central Red Sea show that most scleractinian species release their gametes in the spring,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 83 publications
(190 reference statements)
1
12
0
Order By: Relevance
“…The use of molecular methods allows for the detection of eggs and larvae, which may not be visible in morphological studies. While little is known about the spawning periods of benthic fauna, with the exception of some coral and echinoderms 120 , 121 , colonization of ARMS plates by eggs or larvae and the predators consuming them could have an impact on the community assemblages.…”
Section: Discussionmentioning
confidence: 99%
“…The use of molecular methods allows for the detection of eggs and larvae, which may not be visible in morphological studies. While little is known about the spawning periods of benthic fauna, with the exception of some coral and echinoderms 120 , 121 , colonization of ARMS plates by eggs or larvae and the predators consuming them could have an impact on the community assemblages.…”
Section: Discussionmentioning
confidence: 99%
“…Of the few reproduction studies that have been conducted, Entacmaea quadricolor and Heteractis crispa were found to be gonochoric, releasing their gametes in broadcast spawning events in the austral summer and autumn in subtropical Australia (Scott & Harrison, , , ). In the Red Sea, male Stichodactyla mertensii have been observed spawning on three consecutive days after a boreal spring full moon (Bouwmeester, Gatins, Giles, Sinclair‐Taylor, & Berumen, ). In the laboratory, most E. quadricolor planulae metamorphose within two weeks, although they can remain free‐swimming for at least two months (Scott & Harrison, ).…”
Section: Introductionmentioning
confidence: 99%
“…Actiniaria, biogeography, Cnidaria, connectivity, coral reef, gene flow, Indo-Pacific, microsatellites, phylogeography, population genetics 2007, 2009). In the Red Sea, male Stichodactyla mertensii have been observed spawning on three consecutive days after a boreal spring full moon (Bouwmeester, Gatins, Giles, Sinclair-Taylor, & Berumen, 2016). In the laboratory, most E. quadricolor planulae metamorphose within two weeks, although they can remain free-swimming for at least two months (Scott & Harrison, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Such annual spawning events have been shown to be closely tied to factors such as annual temperature variation, lunar cycles and photoperiod length (Boch et al 2011;Sweeney et al 2011;Keith et al 2016). To date, Invertebrate species other than scleractinian corals have received noticeably less attention with regard to reproduction and this is particularly relevant for the Red Sea, where only very few studies have been conducted on multi-species broadcast spawning (Bouwmeester et al 2016). Here we describe spawning observations of 23 non-coral invertebrates belonging to six species and two phyla.…”
Section: Introductionmentioning
confidence: 99%